Between pressure to act and framework for action – the actors in the German and Swiss vocational education and training systems in the face of digitalisation - Hippach-Schneider, Ute [Verfasser]; Rieder, Elena [Verfasser] (My University, 2022)
"The governance of Vocational Education and Training (VET) systems in Germany and Switzerland is determined by a constellation of actors that has grown over many years. This constellation has long-term elements and at the same time it is a flexible system that is subject to constant pressure to change, just like the economic and social structures that support them. One driver of change in recent years is undoubtedly the so-called digitalisation, which has set in motion sustainable processes of change in companies, called Industry 4.0. These dynamic developments can lead to a change in the distribution of roles among the actors. An appropriate analysis contributes to highlighting the differences in the governance structures of the two systems. The article shows the relevance of the different legal frameworks for the actors’ options for action in the context of digitalisation and its consequences on the adaptability of the two VET systems. Furthermore, it points out some areas of conflict in the respective actor constellations." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S System beruflicher Bildung; S 4.3 Steuerung; S 3.5 Institutionen der Berufsbildungsforschung & -politik; I 2.2.1 Westeuropa; 370; Berufsbildungspolitik; Berufsbildungssystem; Governance; Steuerung; Digitalisierung; Internationaler Vergleich; Bundesrepublik Deutschland; Schweiz